Diet and Psoriasis: Part I. Impact of Weight Loss Interventions - Debbaneh, Maya (2014)
One of the most frequently asked questions by patients with psoriasis is whether dietary changes can improve their condition. Included in this discussion is whether dietary weight loss can benefit their skin disease. Obesity has been associated with a pro-inflammatory state and several studies have demonstrated a relationship between body mass index (BMI) and psoriasis severity. However, the question of whether weight loss interventions can impact psoriasis outcome is less clear. Here, we review the literature to examine the efficacy of weight loss interventions, both dietary and surgical, on psoriasis disease course.